PRINCIPLE OF PROFESSIONALISM IN CONSTRUCTION CONTRACTS - Japar, Sugiarto Raharjo (Journal of Scientech Research and Development, 2024)
The principle of professionalism in construction contracts is a fundamental aspect to ensure the sustainability and safety of a construction project. Construction activities that involve numerous workers, equipment, and risks require comprehensive management. Risk management becomes a vital component in preventing work-related accidents and ensuring security, particularly during the pre-contract and project implementation stages. This study employs a normative legal research method with a focus on statutory analysis. This research aims to provide an in-depth and comprehensive analysis of the importance of applying the principle of professionalism in construction contracts, with a primary focus on up-front risk assessment and risk control. Through a systematic literature review, this research presents an overview of the unique characteristics of construction projects, risk identification, and mitigation strategies that can be implemented by stakeholders to ensure professionalism in construction project management. In conclusion, professionalism is essential for the success and long-term sustainability of construction projects. By implementing comprehensive risk management strategies, construction professionals can effectively identify, assess, and mitigate a diverse range of risks, upholding professionalism that is crucial for the industry's prosperity. Through the strategic application of risk management tools and techniques, these professionals can enhance project efficiency, minimize uncertainties, and balance potential threats and opportunities, ultimately delivering safe, high-quality, and financially viable construction projects.